PERAN FULL DAY SCHOOL TERHADAP PERKEMBANGAN KREATIVITAS DAN SENI PADA SISWA TINGKAT SEKOLAH DASAR - Arif Hidayat; Rizka Febriyani Awliyah; Suyadi Suyadi (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2020)
The purpose of this study was to obtain information about the development of creativity and art in full-day schools. This study used a qualitative method with the type of library research. Full day school was an integrated curriculum and integrated activity, which meant a system that was carried out consciously in order to organize a planned learning action, then implemented and evaluated the learning in a fun way, with the expectation that students did not feel bored and tiresome even though they had studied all day long. The results of the study revealed the schools that implemented the full day school system, seen from previous research or library research, had many significant advantages in the development of creativity and art, one of which was extracurricular activities that could support students' talents and creativity. Some of them were sports, art and musicextracurricular, or extracurricular of science and robotics, from this explanation, the researchers yielded hypothesis that full-day school had an impact on students’ development, especially on creativity and art at the elementary school level.